An investigation into the frequency of negative appendectomies and contributing factors in patients with suspected acute appendicitis - Islam, M. Shahidul; Naznin, Kazi Nasid; Sarker, Tanay Kumar; Jahan, Nusrat; Ali Siddiquee, Muhammad; Reza, Nahid; Faizi, Aklima Parvin; Ovi, Mir Rasekh Alam; Rahman, Ayesha; Shashi, Sanjana Sharmin (International Surgery Journal, 2025)
Background: Acute appendicitis is a common cause of acute abdominal pain in young adults, with varying diagnosis accuracy leading to a significant rate of negative appendectomies, particularly in females and younger patients. This study aimed to evaluate the prevalence of negative appendectomy in patients with suspected acute appendicitis. Methods: A cross-sectional study was conducted at Dhaka medical college hospital from January 2022 to June 2024, involving 220 patients diagnosed with suspected acute appendicitis. Clinical history, examination, and relevant pre-operative investigations were performed. All patients underwent surgery, and histopathological examination of the excised appendices was conducted. Results: Acute appendicitis was confirmed in 175 patients (79.55%), with the highest incidence in individuals aged 10-19 years (54.1%). The negative appendectomy rate was 20.45%, with significantly higher rates in females (77.8%) compared to males (22.2%) (p=0.004). Younger patients (age <20 years) also showed a higher rate of negative appendectomy (33.3%) (p=0.012). Common presenting symptoms included anorexia (66.7%), elevated temperature (>99.4° F) (60%), and localized tenderness in the right iliac fossa (77.8%). Of the 64 patients who underwent pre-operative ultrasound, 63% experienced negative appendectomy. Histopathological examination revealed that 45 patients (20%) were diagnosed as not having appendicitis, with alternative conditions identified in several cases. Conclusions: The study highlights a significant rate of negative appendectomies, particularly in younger females. While clinical judgment plays a crucial role in diagnosis, the findings suggest a need for enhanced diagnostic imaging techniques to reduce unnecessary surgical interventions.